Diffusion approximation for transport equations with dissipative drifts - Persio, L. Di; Kondratiev, Yu. G.; Vardanyan, V. (Methods of Functional Analysis and Topology, 2022)
We study stochastic differential equations with a small perturbation parameter. Under the dissipative condition on the drift coefficient and the local Lipschitz condition on the drift and diffusion coefficients we prove the existence and uniqueness result for the perturbed SDE, also the convergence result for the solution of the perturbed system to the solution of the unperturbed system when the perturbation parameter approaches zero. We consider the application of the above-mentioned results to the Cauchy problem and the transport equations. Вивчаються стохастичні диференціальні рівняння з невеликим параметр збурення. За умови дисипативності коефіцієнту дрейфа у випадку, коли дрейф та коефіцієнти дифузії задовольняють локальній умови Ліпшица, доведено існування та єдиність розв’язку збуреного стохастичного диференціального рівняння. Також отримано результат про збіжність розв’язку збуреної системи до розв’язку незбуреної системи у разі коли параметр збурення прямує до нуля. Розглянуто застосування вищезазначених результатів до задачі Коші та рівняння транспорту.